HDL Functions—Current Status and Future Perspectives - Yasuhiro Endo; Masanori Fujita; Katsunori Ikewaki (Biomolecules, 2023)
Cardiovascular disease (CVD) is the leading cause of death in Western countries. A low HDL-C is associated with the development of CVD. However, recent epidemiology studies have shown U-shaped curves between HDL-C and CVD mortality, with paradoxically increased CVD mortality in patients with extremely high HDL-C levels. Furthermore, HDL-C raising therapy using nicotinic acids or CETP inhibitors mostly failed to reduce CVD events. Based on this background, HDL functions rather than HDL-C could be a novel biomarker; research on the clinical utility of HDL functionality is ongoing. In this review, we summarize the current status of HDL functions and their future perspectives from the findings of basic research and clinical trials.